Responsible Mining Governance: Minimizing Environmental Impact for a Better Future - Marilang (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2024)
Mining management regulations aim to create new buildings that meet the needs of the community. Good mining management can transform Indonesia into the country with the strongest economy in the world through the implementation of the concept of Indonesia. The proposal aims to strengthen the character of the NKRI as a legitimate state and prosper its people through the exploitation of mineral resources. This study has already demonstrated Indonesia's responsibility for building communities in mining areas under Article 33 UUD 1945. The Mining Management System in the national legal system is intended to organize mining with a vision of the welfare state. This prompted him to strengthen the legislation as the basis for the validity of a national mining policy. Mining governance is framed in a legal framework of social justice as a manifestation of the welfare state. Mining activities that do not prosper the people will lose their legitimacy (Pancasila), constitutional (UUD 1945), and social. Total mining governance is based on the principle of sustainable development for the well-being of the people.